2021
DOI: 10.1097/opx.0000000000001747
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Steroid-induced Ocular Hypertension in a 6-year-old Boy

Abstract: SIGNIFICANCE: Systemic corticosteroid use in children is rare because of known risks of adverse effects. The increased prevalence of multisystem inflammatory syndrome associated with COVID-19 may change this. It is critical for eye care providers to be aware of potential severe and rapid ocular hypertensive response to prevent irreversible vision loss. PURPOSE:The purpose of this study was to report the importance of early monitoring of intraocular eye pressure in pediatric patients on systemic steroid medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Steroid is well known to produce ocular hypertension, which may necessitate glaucoma therapy to reduce the intraocular pressure (IOP) to eliminate the symptoms associated with the acute surge in IOP and prevent potential visual field loss. 83 The administration of steroids for treatment of COVID-19 was also reported to result in central serous chorioretinopathy. 84 In a series of 7 COVID-19 cases complicated by endogenous endophthalmitis, 6 cases were secondary to mucormycosis-associated sinusitis or systemic fungal infections, and all had received intravenous corticosteroid for COVID-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid is well known to produce ocular hypertension, which may necessitate glaucoma therapy to reduce the intraocular pressure (IOP) to eliminate the symptoms associated with the acute surge in IOP and prevent potential visual field loss. 83 The administration of steroids for treatment of COVID-19 was also reported to result in central serous chorioretinopathy. 84 In a series of 7 COVID-19 cases complicated by endogenous endophthalmitis, 6 cases were secondary to mucormycosis-associated sinusitis or systemic fungal infections, and all had received intravenous corticosteroid for COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of review, there have been no reports on adverse ocular effects of remdisivir and anti–SARS-CoV-2 monoclonal antibodies in the literature. Steroid is well known to produce ocular hypertension, which may necessitate glaucoma therapy to reduce the intraocular pressure (IOP) to eliminate the symptoms associated with the acute surge in IOP and prevent potential visual field loss 83 . The administration of steroids for treatment of COVID-19 was also reported to result in central serous chorioretinopathy 84 .…”
Section: Resultsmentioning
confidence: 99%
“…Takasi's study reported headaches as a raised IOP symptom [29]. Another study by Prasad et al mentioned blurring of vision, eye pain, redness, lacrimation, and colored halos [31].…”
Section: Symptomatic Vs Asymptomatic Presentationmentioning
confidence: 98%
“…Out of nine, two are retrospective cohort studies [30,33], five are prospective cohort studies [31,32,34,35,36], and one is both a retrospective and prospective cohort study [37]. Three studies out of 12 are case reports [27,28,29], and one is cross-sectional [26]. All studies involved pediatric populations being treated via the systemic route of steroid administration for prolonged periods for various medical conditions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation